FINANCIAL LITERACY AND ITS IMPACT ON LOAN PERFORMANCE: SOME EVIDENCE FROM SAVING AND LOAN COOPERATIVES IN INDONESIA - Wahyudiono, Bambang; Iryani, Lia Dahlia (Universitas Pakuan, 2025)
ABSTRACTThe objective of this study is to examine whether the savings and loan cooperative (SLC), through financial literacy, to increase loan performance quality and the business capacity of members as institutional owners. The research sample was selected using questionnaires with five Likert scales. Research population and sample take location in five Java provinces in Indonesia, which represent 150 SLC or 15 percent of the total provinces in Indonesia. The research method was quantitative, and the analysis technique used SEM PLS. The results of this study indicate that saving and loan cooperative management innovations through the provision of business assistance, marketing consulting, and financial literacy affect the credit performance of their institution. Research findings can play a pivotal role of microfinance institutions (MFIs to support members' businesses and strengthen literacy through institutional regulations. This research can assist microfinance institution management to strengthen the organization's strategic role in financial intermediation and empower micro and small entrepreneurs as members in line with the dual economic and social mission.ABSTRAKTujuan dari penelitian ini adalah untuk mengkaji apakah koperasi simpan pinjam (KSP) melalui literasi keuangan dapat meningkatkan kualitas kinerja pinjaman dan kapasitas usaha anggota sebagai pemilik institusi. Sampel penelitian dipilih menggunakan kuesioner dengan skala Likert lima poin. Populasi dan sampel penelitian berlokasi di lima provinsi di Jawa, Indonesia, yang mewakili 150 KSP atau 15 persen dari total provinsi di Indonesia. Metode penelitian yang digunakan adalah kuantitatif dan teknik analisisnya menggunakan SEM PLS. Hasil penelitian ini menunjukkan bahwa inovasi manajemen koperasi simpan pinjam melalui penyediaan bantuan usaha, konsultasi pemasaran, dan literasi keuangan memengaruhi kinerja kredit institusi mereka. Temuan penelitian ini dapat memainkan peran penting bagi lembaga keuangan mikro (LKM) untuk mendukung usaha anggota dan memperkuat literasi sesuai dengan peraturan institusi. Penelitian ini dapat membantu manajemen lembaga keuangan mikro untuk memperkuat peran strategis organisasi dalam intermediasi keuangan dan pemberdayaan pengusaha mikro dan kecil sebagai anggota, sejalan dengan misi ganda ekonomi dan sosial.